Assessing Students’ College of the Physical Education and Sport Sciences’ Level of Performance in English in Terms the New Prescribed Textbook “New Headway plus” - Sahib Ali, Noor Abdul (Opción, 2019)
The present study intends at assessing the level of ESP university students’ performance in English by using the textbook ‘’ New Headway Plus’’. The de- sign of the present study is a descriptive research. The test has been construct- ed, which consists of one question only with 20 items to investigate students performance level . Face validity, reliability coefficient and item analysis of the test have been computed. The test has been applied on 100 students of the 3rd stage at university of Baghdad / College of Physical Education and Sport Sciences. One – Sample T-Test equation have been used in order to analyze the collected data and find out the results. Final results expose that the ESP students have proved to be good in their performance level because they have been taught by the New Headway Plus textbook. Finally, Conclusions and Recommendations have been stated.